2012
DOI: 10.1109/tdei.2012.6148518
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis ageing status of natural ester-paper insulation and mineral oil-paper insulation by polarization/depolarization current

Abstract: Polarization and Depolarization Current (PDC) technique is an effective tool to assess the condition of oil-paper insulation system in power transformers. So far the PDC behaviors of mineral oil-paper insulation have been widely investigated. However, with the increasing number of transformer choosing natural ester as its insulation oil, it is important to investigate the PDC characteristics of natural ester-paper insulation to see whether the PDC technique can also be used to assess the condition of new insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(17 citation statements)
references
References 25 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…The largest differences between esters and oils are in the range between 400-200 DP. In the studies [19,[40][41][42] it was shown that the paper ages more slowly in esters than in insulating oils. The reason for this is the assumption that esters dry out the paper due to their higher water solubility and thus reduce the hydrolysis processes of the paper.…”
Section: Degree Of Polymerizationmentioning
confidence: 99%
“…The largest differences between esters and oils are in the range between 400-200 DP. In the studies [19,[40][41][42] it was shown that the paper ages more slowly in esters than in insulating oils. The reason for this is the assumption that esters dry out the paper due to their higher water solubility and thus reduce the hydrolysis processes of the paper.…”
Section: Degree Of Polymerizationmentioning
confidence: 99%
“…The insulation system is a type of "transformer heart". Due to the fact that it consists of solid (cellulose and aramid paper) and liquid (electrical insulating liquid), it may degrade mainly due to thermal stresses, but also electrical, mechanical, and chemical stresses occurring in the transformer operating state [8,9]. As a consequence, it may lead to transformer failure, i.e., affect its operational safety [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more attention is paid on the application of Polarization and Depolarization Current (PDC) method to evaluate the insulation state. J. Hao evaluated the natural ester-paper insulation and mineral oil-paper insulation and concluded that an exponential relation between the stable depolarization charge quantity of both kinds of oil-paper insulation sample and the degree of polymerization of paper could be obtained [11]. Based on PDC, G. Ye analyzed the aging degree of XLPE cables with water trees.…”
Section: T W Dakin Evaluated the Aging State Of Insulating Materialmentioning
confidence: 99%